A Case of Fulminant Hepatitis Induced by Measles in an 8-Month-Old Female - Mujtaba, Muhammad; Khan, Ayesha; Gul, Saman; Sherazi, Farida; Naz, Irum (International Journal of Pathology, 2025)
Background: Measles is a common viral infection in children that is self-limiting, but the fulminant hepatitis induced by measles is a very rare case. And we present the case of fulminant hepatitis induced by measles in an 8-month-old female. Case presentation: we have a patient of an 8-month-old female who presented to pediatric OPD with a complaint of fever for 8 days. Clinically, she was diagnosed as a case of measles with complications (pneumonia). After 2 days of admission, she developed seizures, irritable movement, bruises, and abdominal swelling. Emergency management was started for resuscitation and ultrasound abdomen, and ALT was advised on ultrasound. Minimal ascites, gall bladder edema, and hepatomegaly were reported, and LFTs were advised by the radiologist, and ALT was 1582 U/L. At that time, she was suspected of a case of fulminant hepatitis. We put her on symptomatic treatment for liver and coagulation issues. Her symptoms improved. As far as our literature search is concerned, this is the first case to be submitted for case report in Khyber Pakhtunkhwa.